Analisis ECM Budidaya Pembenihan Ikan Gurame di Desa Sidomulyo Kecamatan Semboro Kabupaten Jember - Salsabila, Isqini; Lailatul, Nurul (KUBIS, 2023)
The success of farming is inseparable from several things, one of which is the factor that influences the income of the carp hatchery business, this is to support the increase in carp production in Sidomulyo Village, Semboro District, Jember Regency. The problems faced are related to cultivation that is not optimal, not knowing what factors affect income in their business. This study aims to determine what factors affect income in the long term and short term. Data collection uses existing secondary data.Respondents in this study used purposive sampling, namely 1 respondent. The results of the analysis use the Error Correction Model analysis where the variable number of seeds, demand, pelleted feed, silk worms, and organic supplements that are significant in the long term are the demand variable with a probability value of 0.0000<0.5 and pelleted feed with a probability value of 0.0289<0.5, while in the short term, what is significant is the demand variable with a probability value of 0.0005 <0.5.Based on the results of the study, the variables that have a significant effect on income in the long term are demand and pellet feed, while in the short term, demand.